Development Guidelines for Elderly Potential Enhancement Towards Labor Market Re-entry in the Bangkok Metropolitan Area - จันทร์ทิพย์, ณัฏฐชัย (The Journal of Development Administration Research, 2025)
This study aimed to develop a structural equation model of the influencing factors affecting the potential development of the elderly returning to the labor market in Bangkok. A quantitative research approach was employed, with a sample of 400 individuals aged 60 years and over residing in Bangkok. Data were collected using a questionnaire and analyzed through Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). The results revealed that the model consisted of four key factors are high level and effect follow by: the needs of the elderly, the readiness of the elderly, behavioral transferability and the role of government. The developed model demonstrated a good fit with the empirical data (p = 0.053, CMIN/DF = 1.21, CFI = 0.99, GFI = 0.96, AGFI = 0.94, RMSEA = 0.023, RMR = 0.008, SRMR = 0.015, CN = 434). All four factors positively influenced the potential development of the elderly returning to the labor market and accounted for 90% of the explained variance. The findings provide useful information for policy formulation to support the effective and sustainable reintegration of elderly individuals into the labor force